Fungal laccase-mediated humification of estrogens in aquatic ecosystems. (1st December 2019) - Chen, Mingyu; Waigi, Michael Gatheru; Li, Shunyao; Sun, Kai; Si, Youbin
Abstract: Estrogens are a category of non-degradable organic pollutants prevalent in aquatic environments with reported health risks in human and wildlife reproduction. A biotechnological approach is proposed for utilizing fungal laccase-mediated humification reactions (L-MHRs) to remove estrogens from water. Through a reactive radical-mediated C–C, C–O–C, or C–N–C covalent coupling mechanism, multifarious complex polymeric structures are generated having limited solubilities, which significantly reduces their estrogenic activity and ecotoxicity. This review highlights the available literature associated with the self/cross-coupling mechanism of fungal L-MHRs in catalyzing the single-electron oxidation of estrogens and humic acid (HA). Advances in identifying unknown estrogen-HA cross-coupling products using high-resolution mass spectrometry combined with 13 C-isotope labeling and 13 C NMR may provide key research directions beneficial to aquatic ecological restoration measures. Graphical abstract: Image 1 Highlights: Recent advances in L-MHRs have uncovered the coupling pathway of estrogens and HA. Fungal laccases are beneficial in the removal of estrogens from water. Estrogens are stepwise-polymerized to produce diverse coupling products by fungal L-MHRs. A method is proposed and developed to identify unknown cross-coupling products.